Reductive Activation of O22- from Vanadium(IV) Amidate Species - Drouza, Chryssoula; Papanikolaou, Michael; Hadjithoma, Sofia; Keramidas, Odysseas; Themistokleous, Alexandros; Hayes, Sofia C.; Lianos, Panagiotis; Tsipis, Athanassios C.; Kabanos, Themistoklis A.; Keramidas, Anastasios D.; Amoiridis, Aggelos (My University, 2024)
The two electron reductive activation of O2 to O2 2- is of particular interest to scientific community mainly due to the use of peroxides as green oxidants and in powerful fuel-cells. Among the metal-ions which activate O2, vanadium is of particular interest because of its numerous oxidative catalytic properties. Reaction of either VIVOSO4 .3.5H2O or VIVOCl2 with N- (8-quinolyl)pyridine-2-carboxamide (Hpbq) in CH3OH solution under atmospheric O2, at room temperature, resulted in the quick formation of [VVO(k 2 -O2)(pbq)(H2O)](1). Compound 1 constitutes a rare example of formation of a (peroxo)oxidovanadium(V) complex from molecular O2 and an oxidovanadium(IV) complex. The reaction of formation of compound 1vs. time was monitored by 51V and 1H NMR, UV-vis, cw-X-EPR, Resonance Raman spectroscopiesand cyclic voltammetry revealing the formation of a stable radical intermediate [VVO(k 2 -O2)(pbq)(H2O)]•+ . Dynamic experiments in combination with computational calculations were used to elucidate the mechanism of the reaction. The galvanic cell {Zn|VIII,VII||cis-[VVO2(bpq)], [VVO(O2)(bpq)(H2O)],[VIVO(bpq)(H2O)2] + |O2|C(s)} was manufactured, demonstrating that this technology can be used in Zn|H2O2 fuel cells generating H2O2 in situ from atmospheric O2. Acknowledgements: This work was co-funded by the European Regional Development Fund and the